1994
DOI: 10.1128/aac.38.5.931
|View full text |Cite
|
Sign up to set email alerts
|

Killing of Pseudomonas aeruginosa during continuous and intermittent infusion of ceftazidime in an in vitro pharmacokinetic model

Abstract: An in vitro pharmacokinetic model mimicking human serum drug concentrations, based on a dialyzer unit, was developed to study the efficacies of continuous infusion and intermittent administration of ceftazidime over a period of 36 h. The daily dose of ceftazidime was 300 mg/liter/24 h given either as a continuous infusion or as three bolus doses. The intermittent dosing regimen yielded peak and trough concentrations after the fourth dose of 92.3 (standard deviation, 8.0) and 1.4 (standard deviation, 0.9) mg/li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
197
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(210 citation statements)
references
References 27 publications
10
197
0
1
Order By: Relevance
“…(Table 1b) By contrast to that shown for fluoroquinolones [14], the possibility of selecting resistant mutants at serum piperacillin concentrations <4 MIC is not supported by experimental data. However, several authors have suggested that prolonged percentage of time during which the concentration remains above 4 MIC (T>4 MIC), instead of T>MIC, is an important pharmacokinetic/pharmacodynamic (PK/PD) parameter that better predicts treatment outcome with -lactams (especially for critically ill patients) [2,5,15]. Here,…”
Section: Discussionmentioning
confidence: 99%
“…(Table 1b) By contrast to that shown for fluoroquinolones [14], the possibility of selecting resistant mutants at serum piperacillin concentrations <4 MIC is not supported by experimental data. However, several authors have suggested that prolonged percentage of time during which the concentration remains above 4 MIC (T>4 MIC), instead of T>MIC, is an important pharmacokinetic/pharmacodynamic (PK/PD) parameter that better predicts treatment outcome with -lactams (especially for critically ill patients) [2,5,15]. Here,…”
Section: Discussionmentioning
confidence: 99%
“…Animal and in vitro studies conducted during the 1980s and early 1990s have particularly emphasized the consistently greater efficacy of continuous infusion or more frequent dosing of beta-lactams against Gram-negative bacteria. Although this supported the potential advantage of using continuous and prolonged infusions, the clear superiority of these methods over intermittent dosing had yet to be demonstrated (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Historical Reviewmentioning
confidence: 99%
“…Good quantitative analyses of the pharmacodynamics of antibiotics have been undertaken, in which time-kill curves and the postantibiotic effect are used to estimate the time-killing effect, while MIC and MBC are usually used to estimate the concentration-killing effect. The MIC at which 50% of isolates are inhibited (MIC 50 ), the MIC 90 , and the MIC 99 have sometimes been determined (6,26,29,33,37). However, information on the dynamics of the direct bactericidal effects of antibiotics on bacteria is fragmentary.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when sustained concentrations greater than five times the MIC are used in a two-compartment pharmacokinetic model mimicking human serum drug concentrations, continuous administration is more efficacious than intermittent dosing. Pharmacokinetic-pharmacodynamic models that describe bacterial growth and killing in the presence of antibiotics with pharmacokinetics that mimic those in humans have been developed (26,27). This approach is suitable for description of the development of mutations in inocula exposed to antibiotics in vivo.…”
Section: Derivation Of a New Equation Fitting The Concentration-killimentioning
confidence: 99%